MADAGASCAR: TRADITIONAL EDUCATIONAL PRACTICES AS INDIVIDUAL AND SOCIAL CONSTRUCTION IN PRIMARY SCHOOLS - Iavo, Ramananarivo (Universitas Pendidikan Indonesia, 2020)
This article talks about the science of social education with the primary education system that has been the subject of social construction in Madagascar. Madagascar, starting from education based on traditional education, also opting for the evolution of modern education as in the whole world. the article analyzes the evolution of the life of the society which adopts this traditional education to those of the new education. the students are heirs of the culture but the stakes related to the socio-political vagaries, the new methods, and the traditional method remains predominant in teaching practices and favors this traditional educational practice.